Development of ammophos production technology from Аlgerian phosphorites - Vakal, Sergiy; Karpovych, Eduard; Malyovannyi, Myroslav; Stokalyuk, Oleh (Publishing House of Lviv Polytechnic National University, 2014)
Technological aspects of ammophos production using Algerian phosphorites as a raw material have been investigated. The necessity of increased consumption of sulphuric acid during the Algerian phosporites processing compared with apatite processing has been grounded. The dependence of pH solution on NH3:H3PO4 molar ratio has been determined during neutralization of extraction phosphoric acid prepared from Algerian phosphorites. The necessity of acid solution deeper neutralization in the technology of extraction phosphoric acid production has been proved. The boundary drying temperature of ammonia pulp has been determined. The relation between ammonium nitrogen and drying time has been specified.Досліджено технологічні аспекти виробництва амофосу за умови використання як сировини алжирських фосфоритів. Обґрунтована необхідність підвищених витрат сульфатної кислоти при перероблення алжирських фосфоритів у порівнянні із технологією перероблення апатитового концентрату. Встановлено залежність рН розчину від молярного співвідношення NH3:H3PO4 при нейтралізації екстракційної фосфатної кислоти, виготовленої із алжирських фосфоритів. Доведено потребу більш глибокої нейтралізації кислотного розчину у технології отримання екстракційної фосфатної кислоти із алжирського фосфориту. Обґрунтовано граничну температуру сушіння амонізованої пульпи. Встановлені залежність втрати амонійного азоту від часу сушіння.
Розроблення технології одержання амофосу із Алжирських фосфоритів
Keywords: ammophos; phosphorite; apatite; concentrate; acid; pulpамофос; фосфорит; апатит; концентрат; кислота; пульпа